The Ethos of Care in Manuel Puig’s El beso de la mujer araña - Brock, Ashley (Revista Canadiense de Estudios Hispánicos)

(untitled) (Asociación Canadiense de Hispanistas, 2021)
This article focuses on corporeal experience and the material and affective practice of care in Manuel Puig’s El beso de la mujer araña. It contends that at the heart of the novel’s political project lies an ethos of care that is situated rather than transcendent, contaminated rather than pure, embodied rather than abstract, and transactional rather than disinterested. In spite of all of the ways such an ethos might seem compromised or insufficient, it succeeds in suspending social mechanisms of exclusion and models for the reader a mode of ethical engagement with the world narrated.